Влюбленный убийца: [роман] / Наталия Антонова - Антонова Наталия Николаевна (Уютный детектив, 2019)
Экземпляры: ф. 17 (20231123) / Инвентарный номер: 66845 / Цена: 10.00 / Авт.знак: А 72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6